STRATEGI PEMBELAJARAN KOOPERATIF DALAM PERSPEKTIF AL-QUR'AN - Mukarromah (FIRDAUS, 2025)
Abstract Activities carried out collaboratively tend to feel lighter, more enjoyable, and are capable of increasing motivation to complete tasks more quickly. In the field of education, this principle of mutual cooperation (gotong royong) is implemented through cooperative learning strategies. This strategy is specifically designed to foster group cooperation and enhance social interaction among students. Currently, the cooperative learning model has been widely applied across various educational levels because it is considered effective in building students' social skills. However, like any other instructional method, cooperative learning strategies are not without their advantages and disadvantages. On one hand, this method is able to increase students' active engagement and learning outcomes. On the other hand, challenges such as unequal role distribution or the dominance of certain individuals within a group often become obstacles in its implementation. Therefore, educators require careful consideration and comprehensive planning in selecting and aligning this strategy with the characteristics of the material and the needs of the learners. This article aims to examine cooperative learning strategies, specifically by analyzing the philosophical foundations and values of such collaboration from the perspective of the Qur'an. Through a literature approach, this study is expected to provide a theoretical contribution for educators in integrating spiritual and social values into modern learning methods, thereby creating a learning process that is not only cognitively effective but also humanistic and deeply meaningful. Keywords: Cooperative Learning Strategies, Student Interaction, Qur'anic Perspective